Quality of life and its determinants in people living with Human Immunodeficiency Virus infection in Kannur District, Kerala - C B Pradeesh; Sahya S Dev; Prathyush Sivadasan; V K Sobhith (Wolters Kluwer Medknow Publications, 2023)
Introduction: The prevalence of Human Immunodeficiency Virus (HIV) infection in India is on decline. Since the introduction of Anti Retroviral Therapy, the survival of HIV positives has improved a lot. HIV/acquired immunodeficiency syndrome (AIDS) is now a chronic yet manageable disease. However, social factors like stigma and discrimination still exist, affecting the quality of life (QoL) of people living with HIV (PLHIV)/AIDS. The objectives of the study were to assess the QOL among HIV-positive patients using the World Health Organization-QOL BREF (WHO-QOL BREF) questionnaire, the factors determining the QoL of HIV-positive patients, and the stigma and discrimination faced by HIV positives in the medical field. Methods: A cross-sectional study was done during the study period of 1 year. A total of 150 PLHIV from Kannur district in Kerala participated in the study. The WHO-QOL BREF, Scale and the HIV stigma scale were used to collect the data. Results: The QoL score found in the study was 15.36 ± 2.18, 2.18. The overall QoL was influenced by education, the Stigma Scale score, having a constant income or an increased income after diagnosis, and a Perceived Social Support Scale score. The study also found that 22% (33) of the participants faced stigma and discrimination from the medical field in one form or another. Conclusion: The study found that the QOL of PLHIV in the Kannur district of Kerala revealed no difference between men and women. The determinant factors for QOL were found to vary in each domain. Education was found to have a negative impact on QOL.